Effects of welding procedures on mechanical and morphological properties of hot gas butt welded PE, PP, and PVC sheets - DEMİRER, HALİL (WILEY-BLACKWELL, 2008)
Mechanical and morphological properties of hot gas butt welds on polyethylene (PE), polypropylene (PP), and polyvinyl chloride (PVC) sheets for four different procedures, which are single and double V-welds with and without a welding shoe, were investigated. Besides, weldabilities of base materials were evaluated by rheological measurements. These revealed that weldabilities of PE and PP sheets were better than that of PVC. Welding energy (E-w), which is transferred onto weld surfaces, was calculated to evaluate weld quality. The results of tensile, impact, and bending tests indicated that the weld strengths of PVC sheets were lower than those of PE and PP sheets. When the welding shoe was used, weld strength increased significantly for each material because of the presence of sufficient welding pressure and the effective heating on surfaces. The best results were attained for the double V-welds with the welding shoe. Morphology of welded regions was evaluated by polarized light, stereo, and scanning electron microscopy. Polarized light microscopy studies indicated that the heat-affected zone (HAZ) consisted of welding rod core, molten zone, and deformed spherulitic zone, and the welding interface was indistinguishable from the base material when the welding pressure was enough.
Keywords: THERMOPLASTICS; POLYPROPYLENE; COMPOSITES; POLYMERS; PLASTICS; JOINTS; HDPE